Pengembangan Herbarium Digital Morfologi Daun Tanaman Dikotil di Lingkungan Kampus UNWAHA - Hanifah, Elsa Ummi; Wulandari, Anggun; Sholihah, Fatikhatun Nikmatus (YASIN, 2025)
This media development is motivated by students’ low comprehension of leaf morphology material and the limitations of conventional learning media, such as physical herbaria that require special care, large storage space, and limited accessibility. The aim of this study is to develop a digital learning medium in the form of a leaf morphology herbarium of dicotyledonous plants, utilizing Instagram as a visual, engaging, and flexible platform suitable for student use. The herbarium was developed using leaf specimens collected from the campus environment of Universitas KH. A. Wahab Hasbullah (UNWAHA). The research adopted the 4D development model (Define, Design, Develop, Disseminate), although the process was limited to the Develop stage due to time constraints. Validation was carried out by media and content experts, yielding feasibility scores of 86% and 89% respectively, both categorized as “highly feasible.” The study concludes that the Instagram-based digital herbarium is a feasible alternative learning medium that is effective, innovative, and aligned with the characteristics of learners in the digital era. The implications of this development include strengthening visual literacy, enhancing access to technology-based learning, and expanding the use of digital platforms in science education.